2016
DOI: 10.3390/nu8050286
|View full text |Cite
|
Sign up to set email alerts
|

Inositol Hexaphosphate and Inositol Inhibit Colorectal Cancer Metastasis to the Liver in BALB/c Mice

Abstract: Inositol hexaphosphate (IP6) and inositol (Ins), naturally occurring carbohydrates present in most mammals and plants, inhibit the growth of numerous cancers both in vitro and in vivo. In this study, we first examined the anti-metastatic effects of IP6 and Ins using a liver metastasis model of colorectal cancer (CRC) in BALB/c mice. CT-26 cells were injected into the splenic capsule of 48 BALB/c mice. The mice were then randomly divided into four groups: IP6, Ins, IP6 + Ins and normal saline control (n = 12 pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 48 publications
1
17
0
Order By: Relevance
“…A possible explanation for this observation is that lower expression of GDE1 converted to less inositol, with less inositol resulting in poorer prognosis. Previous studies have indicated that increasing concentrations of inositol in vivo and in vitro may control cancer metastases and improve quality of life (Bacić et al, 2010;Vucenik & Shamsuddin, 2003;Vucenik & Shamsuddin, 2006;Lam et al, 2006;Abul Kalam, Shamsuddin & Ivana, 2005;Shamsuddin, Ullah & Chakravarthy, 1989;Carlomagno & Unfer, 2011;Fu et al, 2016;Nishino et al, 1999). Supporting evidence for this comes from our survival analysis results, in which higher expression of GDE1 showed better survival in COAD.…”
Section: Discussionmentioning
confidence: 99%
“…A possible explanation for this observation is that lower expression of GDE1 converted to less inositol, with less inositol resulting in poorer prognosis. Previous studies have indicated that increasing concentrations of inositol in vivo and in vitro may control cancer metastases and improve quality of life (Bacić et al, 2010;Vucenik & Shamsuddin, 2003;Vucenik & Shamsuddin, 2006;Lam et al, 2006;Abul Kalam, Shamsuddin & Ivana, 2005;Shamsuddin, Ullah & Chakravarthy, 1989;Carlomagno & Unfer, 2011;Fu et al, 2016;Nishino et al, 1999). Supporting evidence for this comes from our survival analysis results, in which higher expression of GDE1 showed better survival in COAD.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that inositol hexaphosphate and inositol can inhibit chemically induced rat hepatocarcinogenesis (Lee, Lee, & Choi, ). As the backbone and precursor of inositol phosphates, inositol is primarily used to treat diabetes (Dang, Mukai, Yoshida, & Ashida, ), hepatitis (Okazaki, Setoguchi, & Katayama, ), polycystic ovary syndrome (Santamaria et al, ), colorectal cancer (Fu, Song, Wen, Lu, & Cui, ) and other diseases. Inositol exhibits moderate anticancer activity, and it synergistically enhances the inhibitory effects of inositol hexaphosphate on the growth of colon (Shamsuddin, Ullah, & Chakravarthy, ) and mammary cancers (Vucenik, Yang, & Shamsuddin, ).…”
Section: Discussionmentioning
confidence: 99%
“…25 Furthermore, another study in our laboratory established a BALB/c mouse model of colorectal cancer with liver metastasis by injecting the cell line into spleen; results showed that colorectal cancer with liver metastasis could be inhibited in this model when IP6 is combined with INS. 26 This model mimics the vascular diffusion process of colorectal cancer; this process is a characteristic of colorectal cancer with liver metastasis.…”
Section: Introductionmentioning
confidence: 99%